Penerapan Profil Pelajar Pancasila Di Sekolah Dasar (Studi Kasus Di Sekolah Dasar Negeri 193 Pekanbaru) - Yulianda, Sri; Mustika, Dea (Lembaga Yasin AlSys, 2023)
The Pancasila student profile is a national education goal. The Pancasila student profile is a reference for educators in building the character and competence of students. The aim of this research is to find out the application of the Pancasila student profile in the independent curriculum in elementary schools and also to find out the obstacles faced by teachers during its implementation. This research method is qualitative with a case study type. The data collection technique uses interviews, observation and documentation. Data sources involve the school principal, 2 teachers and 2 students. Testing the validity of the data uses triangulation. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The results of the research show that the teacher has implemented the Pancasila student profile even though all of these applications can be realized well by the students themselves. The obstacles faced by teachers in implementing the Pancasila student profile are the different characteristics and abilities of students, lack of motivation from parents and advances in technology. The conclusion from the research results is that the form of implementation carried out by teachers is to familiarize students with always saying greetings, reciting prayers, instilling an attitude of loving tradition, respecting diversity and training students to be able to work together with each other and have an attitude of responsibility.